Proceedings of the SLACTIONS 2009 International Conference - Morgado, Leonel (2009)
Today, text-based communication systems seem to drive most of social media. At the same time, the corporate world gives its first tentative strides with tools such as Twitter, in a search for alternative ways to reach consumers. However, there seems to be a stubbornly faithful community to 3D environments and metaverse platforms, proposing a deep look into what these environments have of new and unique to offer. Whether these metaverses are proprietary (e.g.: Second Life) or open (e.g.: OpenSimulator and Croquet), business-oriented (e.g. Project Wonderland) or arising from research (e.g. mWorlds and Sirikata) , what arguably distinguishes these environments from the abounding textintensive social media is the user’s embodiment and the opportunities for creation through object modelling, including complex behavior programming. This sophistication has its cost and it is not a small one for the currently ‘crisis- hit’ academic institution – metaverse platforms are avid environments for both internet and computer processor speeds; and the users’ learning curve is significant. However, higher education institutions continue to acquire virtual real estate – notably in Second Life - and to release faculty from other, more conservative, tasks, so they have the time to test new forms of teaching (and, to a lesser extent, research) in these environments.